Analisis Faktor Penyebab Time Overrun Proyek Pembangkit Listrik Dengan Pendekatan Partial Least Square Structural Equation Modeling - Ariyanto, Agus Dwi; Armono, Haryo Dwito (Universitas Trunojoyo Madura, 2024)
Power plant projects are crucial to providing andining a reliable power system. Power plant projects, like other construction projects, often experience a problem of delayed completion of work known as time overrun, which can result in financial losses and project failure to be completed on time. Time overrun is overtime that exceeds the completion date specified in the contract or the project submission date agreed by both parties. Engineering, procurement, construction, and commissioning are all parts of the power plant construction project. In completing the project, it is essential to understand why the power plant construction project is delayed and how to properly mitigate the risk. This research is quantitative research, which means using a questionnaire. The aim of this study is to find out what caused the time overrun of the power plant project at the Timorese PLTU. Partial Least Square Structural Equation Modeling (PLS-SEM) is used to process data from questionnaire results. The results of the research showed that there were seven research hypotheses, with two accepted and five rejected. The external factors, and the owner-related factors are the time overrun factors based on the accepted hypothesis. Based on the cause of the time overrun, some mitigation measures can be recommended to management including a memorandum of understanding (MoU) scheme with stakeholders related to existing permits, a scheme related to contractual and technical procedures when unforeseen conditions occur and ensuring the quality of the results of the soil investigation.